Parents' Perception of Staff Support in a Father-Friendly Neonatal Intensive Care Unit - Linn Iren Risanger; Poul-Erik Kofoed; Betty Noergaard; Signe Vahlkvist (MDPI AG, 2023)
Healthcare professionals, especially nurses, play a central role in supporting parents during their stay in neonatal intensive care units (NICUs). Fathers often have their own support needs; however, studies have shown that these needs are rarely met to the same degree as those of the mothers. We developed a "father-friendly NICU" with the aim of providing good-quality care to the entire family. To evaluate the impact of this concept, we adopted a quasi-experimental design; using the Nurse Parent Support Tool (NPST), we investigated the differences in the fathers' (n = 497) and mothers' (n = 562) perception of the nursing support received on admission and discharge between before and after the intervention. In the historical control and intervention groups, the fathers' median NPST scores at admission were 4.3 (range, 1.9-5.0) and 4.0 (range, 2.5-4.8), respectively (p < 0.0001); at discharge, these scores were 4.3 (range, 1.6-5.0) and 4.4 (range, 2.3-5.0), respectively (difference not significant). In the historical control and intervention groups, the mothers median NPST scores at admission were 4.5 (range, 1.9-5.0) and 4.1 (range, 1.0-4.8), respectively (p < 0.001); at discharge, these scores were 4.4 (range, 2.7-5.0) and 4.4 (range, 2.6-5), respectively (difference not significant). The parental perception of support did not increase after the intervention; however, the parents reported a high level of staff support both before and after the intervention. Further studies should focus on parental support needs during the different phases of hospitalization (i.e., admission, stabilization, and discharge).